Effect of diurnal intermittent fasting during Ramadan on ghrelin, leptin, melatonin, and cortisol levels among overweight and obese subjects: A prospective observational study - Al-Rawi, Natheer; Madkour, Mohamed; Jahrami, Haitham; Salahat, Dana; Alhasan, Fatima; BaHammam, Ahmed; Al-Islam Faris, Mo'ez (PLOS ONE, 2020)
Background Levels of cortisol, melatonin, ghrelin, and leptin are highly correlated with circadian rhythmicity. The levels of these hormones are affected by sleep, feeding, and general behaviors, and fluctuate with light and dark cycles. During the fasting month of Ramadan, a shift to nighttime eating is expected to affect circadian rhythm hormones and, subsequently, the levels of melatonin, cortisol, ghrelin, and leptin. The present study aimed to examine the effect of diurnal intermittent fasting (DIF) during Ramadan on daytime levels of ghrelin, leptin, melatonin, and cortisol hormones in a group of overweight and obese subjects, and to determine how anthropometric, dietary, and lifestyle changes during the month of Ramadan correlate with these hormonal changes. Methods Fifty-seven overweight and obese male (40) and female (17) subjects were enrolled in this study. Anthropometric measurements, dietary intake, sleep duration, and hormonal levels of serum ghrelin, leptin, melatonin, and salivary cortisol were assessed one week before the start of Ramadan fasting and after 28 days of fasting at fixed times of the day (11:00 am-1:00 pm). Results At the end of Ramadan, serum levels of ghrelin, melatonin, and leptin significantly (P<0.001) decreased, while salivary cortisol did not change compared to the levels assessed in the pre-fasting state. Conclusions DIF during Ramadan significantly altered serum levels of ghrelin, melatonin, and serum leptin. Further, male sex and anthropometric variables were the most impacting factors on the tested four hormones. Further studies are needed to assess DIF's impact on the circadian rhythmicity of overweight and obese fasting people.